Analisis faktor risiko yang berhubungan dengan kejadian anemia gravidarum - Agnes Ria Angresti Agustina; Heni Puji Wahyuningsih; Niken Meilani (Poltekkes Kemenkes Yogyakarta, 2014)
Background: At Banguntapan I Health Center, Fe coverage has met the target of Fe1 100% and Fe3 87.26%, but the prevalence of pregnancy anemia is high, ie. 40.61%. The result of literature study shows that risk factors associated with the prevalence of pregnancy anemia are age of pregnant mothers, parity, birth spacing, gestation period, level of education, economic status, and status of chronic energy deficiency. Objective: The study aimed to identify correlation between factors of age of pregnant mothers, parity, birth spacing, gestation period, level of education, economic status, and status of chronic energy deficiency with the prevalence of pregnancy anemia at Banguntapan I Health Center 2013. Method: The study was an analytic survey with cross sectional design. Samples were 93 pregnant mothers at Banguntapan I Health Center selected through proportional sampling. Research instruments consisted of data sheet of pregnant mothers, upper arm circumference, digital automatic haemoglobinometer, and table master. Statistical test used univariate, bivariate (Chi square), and multivariate (Logistic Regression Test). Result: Rate of pregnancy anemia was 28%. The result of bivariate test showed risk factors significantly correlated with the prevalence of pregnancy anemia were age of mothers during pregnancy (p-value=0.00), level of education (p-value=0.03), and status chronic energy deficiency (p-value=0.00). The result of multivariate test showed risk factors affecting the prevalence of pregnancy anemia were age of mothers during pregnancy (p-value=0.00) and status of chronic energy deficiency KEK (p-value=0.00). Conclusion: Risk factors correlated with the prevalence of pregnancy anemia at Banguntapan I Health Center in 2013 were age of mothers during pregnancy, level of education, and status of chronic energy deficiency and the most dominant factor was status of chronic energy deficiency.